Is the Charlottenthal fan (marginal zone of the Pomeranian phase, NE Germany) an end moraine? - Pisarska-Jamroży, Małgorzata; Börner, Andreas (Geologos, 2011)
The maximum ice-sheet extent of a glaciation or glacial phase is in most cases indicated by the position of end moraines. In some cases, however, the maximum extent of the ice sheet is indicated by a fan which represents the transitional zone between the end moraine and the proximal outwash plain (sandur). Such a fan from the Pomeranian phase near Charlottenthal in NE Germany has been investigated for its lithofacies, and the depositional mechanisms of the two sedimentary environments (end moraine and outwash plain) are reconstructed. The Charlottenthal is not characteristic in a sedimentological sense of a typical marginal end moraine or a sandur. The deposits represent subaerial debris flows, sheet floods and channelized currents, which are typically processes for transitional fan. Gravel samples from the till complex show typical Weichselian till compositions. These till compositions indicate a general transport direction from North to South, which is consistent with the known movement of the ice sheet during the Pomeranian phase of the Weichselian.